2017
DOI: 10.4038/rjs.v8i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the microbiological quality and proximate composition of fermented cassava food products sold in Ilorin-west local government area, Nigeria

Abstract: In the present study, the microbiological safety and the proximate analyses of five urban markets within Ilorin-West Local Government Area, Kwara State, Nigeria were carried out using standard protocols. The bacterial load of fermented staple products from cassava ranged from 0.1 to 10.9×10 5 CFU/g while the fungi and yeast content ranged from 1.1 to 8.2×105 CFU/g. The isolates of bacteria from all the markets include the following;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
4
10
4
1
Order By: Relevance
“…GAS had higher values of pH, crude protein, fat, fibre, ash, and energy whereas UAS were higher in moisture and crude carbohydrate contents. MAB/TAPC which corroborates earlier literature reports [12,19], but exceeded limits for coliforms (E. coli inclusive) for street vended foods. However, investigators reported much higher counts when Ugba (Pentaclethra macrophylla) and Ogiri (Ricinus comminus) were incorporated into the dish [8,37].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…GAS had higher values of pH, crude protein, fat, fibre, ash, and energy whereas UAS were higher in moisture and crude carbohydrate contents. MAB/TAPC which corroborates earlier literature reports [12,19], but exceeded limits for coliforms (E. coli inclusive) for street vended foods. However, investigators reported much higher counts when Ugba (Pentaclethra macrophylla) and Ogiri (Ricinus comminus) were incorporated into the dish [8,37].…”
supporting
confidence: 90%
“…Several researchers have reported poor personal hygiene, lack of education, ingredients, water and sanitary status of the environment as fundamental predisposing factors of microbial contamination of vended RTE foods [12][13][14][15][16][17][18]. A variety of the microbes (e.g., bacteria, fungi and viruses) reported in RTE foods not only accentuate public health risks but also produce potential toxigenic compounds [4,[19][20][21][22]. Cross/post-contamination may also be associated with insect vectors [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of the samples was higher compared with the moisture content of 58.80% recorded by Omosuli et al (2017) from fufu prepared from cassava flour in their study. It was however lower than the moisture content of 72.25% recorded by Adetunji et al (2017) from fufu gotten from different market in Ilorin West. The different variation recorded in the moisture content of the fufu from the various studies might be due to the fact that some level of transpiration occurs after the processing of cassava tubers into fufu (Ikujenlola et al, 2007).…”
Section: Proximate and Dietary Fibre Composition Of Boiled And Stirred Cassava Fufucontrasting
confidence: 58%
“…84 g/100 g) samples. Adetunji, Akande, Oladipo, Salawu, and Onyegbula (2017), reported lower values (73.47–77.27 g/100 g) for fermented cassava flour obtained from different markets area in the Ilorin West local government area. However, similarly relatively high values (81.55–84.34 g/100 g) have also been reported for fermented cassava flour (Indrastuti, Estiasih, Christanti, Pulungan, & Zubaedah, 2018).…”
Section: Resultsmentioning
confidence: 98%